Assessing Halal Awareness Through Construction of Moderate to The Availability of Products and Sharia Services Performance - Mahsun, Moch; Narto, Narto; Wahyudi, Soedimas; Novita, Mona (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
This misunderstanding regarding the meaning of moderation in religion has implications for the emergence of antipathetic attitudes in society towards caring for halal products, which is only focused on Islamic communities. This has an impact on the phenomenon of the 'basket foreign products' movement, which, in fact, is non-Muslim as if it has become a scourge of 'custom' towards the sacred quality of certified halal products in Indonesia. This bias impacts the performance of retail stores that are committed to providing products that are halal-certified. Even though the construction of a halal guarantee is a 'final thing' and moderated for all groups (including non-Muslims) through concern for halal products as a guarantee that the shop is committed to the halal industrial movement. This urgency requires an assessment and strategy for store performance so that it does not impact the availability of halal products and ensures a competitive advantage for all Muslim and non-Muslim communities in the future. This research was designed with a halal value approach through SOAR Analysis to realize awareness of halal value status and as a competitive advantage for store performance with the principle of moderation. This research hopes to create halal awareness, provide full guarantees, and be able to adapt well and give input to stakeholders